1985
DOI: 10.1038/313647a0
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement and transcription of the β-chain genes of the T-cell antigen receptor in different types of murine lymphocytes

Abstract: Rearrangements of T-cell receptor beta-chain genes are usually found on both chromosomal homologues, occurring by both deletional and non-deletional mechanisms. Two constant-region (C beta) genes have been identified previously and at least one is transcribed in every helper or cytotoxic T cell tested, but the choice of C beta gene expression is not correlated with the specialized functions of these T lymphocytes. By contrast, four of five suppressor T-cell hybridomas examined have deleted all known joining (J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(81 citation statements)
references
References 62 publications
5
76
0
Order By: Relevance
“…). These results agree with an earlier study that demonstrated that EL4 possessed a partial D␤1-J␤1 rearrangement and expressed a full-length C␤2-containing mRNA transcript (49).…”
Section: El4 and Rma Cell Lines Have A Common Originsupporting
confidence: 83%
“…). These results agree with an earlier study that demonstrated that EL4 possessed a partial D␤1-J␤1 rearrangement and expressed a full-length C␤2-containing mRNA transcript (49).…”
Section: El4 and Rma Cell Lines Have A Common Originsupporting
confidence: 83%
“…The simultaneous appearance of both beta 1 and beta 2 rearrange-6.5 Figure 5. Autoradiograph of Southern ments on the same chromosome may be explained by nonproductive Dbeta 2-Jbeta 2 rearrangements (17). SC-5 also demonstrates two beta 1 rearrangements but appears to have one beta 2 rearrangement and a germ-line band.…”
Section: Resultsmentioning
confidence: 99%
“…Restriction enzyme digestion to detect rearrangements at the IgH (EcoRI), Igk (BglII), TCR Jb1 (PvuII), Jb2 (HindIII), and Evi3 (XbaI) loci and Southern hybridization have been detailed elsewhere (Gilbert et al, 1993;Justice et al, 1994). Probes for IgH, Igk, TCR Jb1, and Jb2 have been described elsewhere (Kronenberg et al, 1985;Mucenski et al, 1986). The probe for Evi3 was prepared from a 1 kb KpnI genomic fragment cloned into pBluescript KS þ (Justice et al, 1994).…”
Section: Southern Blot Analysismentioning
confidence: 99%